A Cross-cultural Investigation of Tourists’ Memorable Experiences between Two Nationalities - Gökhan Ayazlar (Almatourism, 2017)
This study aims to make a cross-cultural investigation into tourists’ memorable experiences. A self-administrated survey was carried out between Turkish and British tourists visiting Didim, Turkey, in the summer of 2016. 247 valid questionnaires from Turkish tourists and 241 valid questionnaires from British tourists were collected. Seven dimensions of memorable tourism experiences-hedonism, refreshment, novelty, local culture, meaningfulness, knowledge and involvement - were identified through factor analysis in the study. The results also indicated that British tourists had found local culture more memorable in their travels than Turkish tourists. However, hedonism was the most memorable experience dimension for Turkish tourists. The practical and theoretical contributions of the study results are discussed.